Acute effects of mental recovery strategies in simulated air rifle competitions - Loch, Fabian; Ferrauti, Alexander; Meyer, Tim; Pfeiffer, Mark; Kellmann, Michael (Frontiers in Sports and Active Living, 2023)
Objectives The present study aimed to assess the perception and change of mental and physical fatigue and to examine acute effects of mental recovery strategies in air rifle athletes across simulated competition days with two consecutive competition bouts. Design We conducted a randomized counterbalanced crossover study. Method 22 development air rifle athletes (Mage = 17.77 ± 4.0) of a regional squad participate in the study. The Short Recovery and Stress Scale (SRSS), perception of mental fatigue, physical fatigue, concentration and motivation as well as differential Ratings of Perceived Exertion (RPE) were used to assess recovery-stress states and fatigue states. During a recovery break, participants underwent two mental recovery strategies (powernap, systematic breathing) or a control condition. Total shooting scores were recorded for both competition bouts. Results Study results revealed a significant increase of post ratings for mental (p < .001) and physical fatigue (p < .001) for both competition bouts. The correlation coefficient between change in mental and physical fatigue for both competitions revealed a shared variance of 7.9% and 18.6%, respectively. No significant group-based acute effects of the use of mental recovery strategies on shooting performance, and psychological and perceptual measures were found. On an individual level, results illustrated statistical relevant improvements of shooting performance after powernapping or systematic breathing. Conclusion Mental and physical fatigue increased and accumulated across a simulated air rifle competition and mental fatigue emerged as a separate construct from physical fatigue. The use of strategies to accelerate mental recovery on an individual level (e.g., powernap, systematic breathing) may be a first step to manage a state of mental fatigue, but further studies on mental recovery strategies in an applied setting are needed.